Pendidikan Kesehatan dan Dukungan Suami Menurunkan Postpartum Blues Ibu Pasca Bedah Sesar - Aida Kusnaningsih (Syntax Corporation, 2023)
Postpartum blues are changes in feelings that often occur in post-cesarean mothers, such as feelings of sadness, excessive joy, and feelings of depression, sudden crying, and irritability. Occurs from a few hours to a few days after delivery. Postpartum blues can be overcome with health education and husband's support, so the study aims to determine the effect of providing Health Education and Husband Support on the incidence of Postpartum Blues in Post-Cesarean Section Mothers. Quasi-experimental research design, with a pre-posttest approach. Sampling by consecutive sampling on 60 respondents who were divided into control and intervention groups. Instruments used EPDS, data were analyzed using the Mc Nemar test and Chi Square test. There was a difference in the proportion of postpartum blues events between the intervention group and the control group after the intervention group was given health education and husband support (P Value 0.041). Post-cesarean section mothers who received intervention had a 4.33 times higher chance of not experiencing postpartum blues compared to mothers who did not receive intervention (OR: 4.33; 1.20-15.60). Health education and husband's support influence the incidence of postpartum blues in post-cesarean section mothers.